PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEAD TOGETHER) MENGGUNAKAN PETA KONSEP TERHADAP HASIL BELAJAR FISIKA SISWA - Bahtiar Bahtiar; Musanni Musanni; Laelatul Hapipah (IKIP Mataram, 2013)
This study aims to determine the effect of cooperative learning type NHT (Numbered Head Together) Using Concept Map to physics learning outcomes of VIII grade students og state MTs. 3 Mataram Academic Year 2012/2013. The hypothesis proposed is there is influence of cooperative learning type NHT (Numbered Head Together) using concept map to physics learning result of VIII grade MTs 3 Mataram students Academic Year 2012/2013 Lesson. Type of research used is Quasy experiment. The population in this research is all VIII grade students of state MTs. 3 Mataram. The sample was taken by purposive sampling technique that is VIIIB class as experimental class and VIIIE class as control class in state MTs. 3 Mataram. The data was collected in study by giving pre-test and post-test to the sample class student. Data collection techniques using objective tests that have been tested for validity, reliability, difficulty index, differentiation, and spotting function. Based on the analysis results of pre-test data obtained the average value of the experimental class is 50.4 and the control class is 51.8. Post-test results showed the average experiment class is 73.51 and the control class is 62.42. The sample student's post-test data were analyzed using t-statistical calculations. Based on the result of data analysis using t-statistic obtained t count 4,13 and t table 1.99. From the results obtained t count> t table at 5% error level, this indicates that Ha accepted and Ho rejected. Based on the results of N-Gain test in the experimental class obtained an increase of 0.47 while in the control class there was an increase of 0.22. The improvement of the students' learning outcomes in the experimental class is classified into the medium category and the control class fall into the low category. Thus, the improvement of students' learning outcomes in the experimental class is higher than the control class (0.47> 0.22). This means that the application of cooperative learning model type NHT (Numbered Head Together) using concept map gave a significant contribution to physics learning outcomes of VIII grade students of State MTs. 3 Mataram on the subject of energy and effort.